Preparation of rabbit kidney immortalized cell culture - V. L. Manin; I. V. Vologina; Ye. A. Trofimova (Ветеринария сегодня)
Preparation of immortalized cell lines obtained from organs and tissues of farm animals is an essential area of biotechnology. The paper presents results of continuous (immortalized) cell line preparation from a primary trypsinized cell culture of an adult rabbit kidney. Cytomorphologic analysis and karyotyping were performed during the process of subcultivation in the cell culture at passages 1, 3, 24, 31, 38, 56, 66, 75, 86, 101. Dynamics of spontaneous continuous cell line formation during long-term serial passaging was examined using standard nutrient media and fetal serum. Contrary to the known cell lines of rabbit origin (Oryctolagus cuniculus L.), immortalization was not accompanied with enhanced cell production and cell size reduction. The prepared continuous cell line in its adhesive phase was up to 200 µm in size and its productivity was about 7,000 cells/cm2. Significant differences (compared to the known cell lines) in the karyotype were detected during passaging. The formed genotype was found to be near-tetrapioid when the CCL cultural properties were stabilized at passages 66–101. The known cell lines – rabbit kidney (RK-13) and rabbit cornea (SIRC) – can be characterized as pseudotriploid basing on their karyotype. This culture demonstrated low sensitivity to viruses – causative agents of rabbit diseases and sensitivity to heterologous porcine and bovine viruses.